Correlation between Types of Bleeding Brain Lesion with Glasgow Coma Scale in Head Injury Patients at Gunung Jati Regional Hospital, Cirebon, Indonesia - Tantowijaya, Bibit; Debyanti, Merliana; Kusnandang, Agus (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Head injuries were a leading cause of morbidity and mortality worldwide, often resulting in bleeding brain lesions such as epidural hematoma, subdural hematoma, subarachnoid hemorrhage, and intracerebral hematoma. The Glasgow Coma Scale (GCS) was a widely used tool to assess the level of consciousness in head injury patients. Understanding this relationship was essential for guiding clinical management and predicting patient outcomes, especially in regions with high incidences of traumatic brain injuries, such as Cirebon, Indonesia. Aims: To analyze the relationship between bleeding brain lesions and the Glasgow Coma Scale in head injuries at Gunung Jati Regional Hospital, Cirebon, Indonesia. Methods: This study used an analytical observational method with a cross-sectional approach. Data collection was conducted using total sampling with a sample size of 28. The inclusion criteria were patients with CT-confirmed brain hemorrhages (epidural, subdural, subarachnoid, or intracerebral hematomas). Data were obtained from medical records in 2023 at Gunung Jati Regional Hospital. The analysis was performed using the Spearman rank correlation test to evaluate the relationship between the type of brain hemorrhage and GCS scores. Results: The total sample of 28 included 21 patients (75%) with Intracerebral Hematoma, 3 patients (10.7%) with Subdural Hematoma, 2 patients (7.1%) with Epidural Hematoma, and 2 patients (7.1%) with Subarachnoid Hematoma. The level of consciousness in these patients was as follows: 15 patients (53.6%) with mild injuries, 8 patients (28.6%) with moderate injuries, and 5 patients (17.9%) with severe injuries. Spearman correlation analysis showed no significant relationship between Bleeding Brain Lesions and Glasgow Coma Scale in head injuries (p =0.645). The absence of correlation might have been due to unaccounted factors in this study, such as hemorrhage volume, lesion location, midline shift, and injury mechanism. Conclusion: There is no significant relationship between types of bleeding brain lesions and Glasgow Coma Scale in head injury patients. The study's limitations included a small sample size and the exclusion of variables such as hemorrhage volume and location, which could affect the level of consciousness. Future research was recommended to involve larger sample sizes and additional clinical factors to better understand the dynamics between types of brain hemorrhages and patients' levels of consciousness, potentially improving clinical management strategies.